2023
DOI: 10.3390/f14071501
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Comfort Analysis and Optimization Strategies of Green Spaces in Chinese Traditional Settlements

Abstract: The spatial pattern of Weizi settlements features distinct regional characteristics. Moreover, it contains profound wisdom in terms of traditional construction; therefore, studies on its association with the microclimate have important implications for improving the quality of human settlements. In the present study, Guanweizi Village in the Xinyang City of Henan Province was used as an example to analyze and evaluate the thermal comfort of green spaces. The impact of peripheral water bodies on the thermal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Meanwhile, they summarized the recommended values of spatial characteristics and visual and smell environment indicators. Cheng et al analyzed the factors affecting the thermal comfort of green spaces [15]. They found that water and greening coverage are the primary factors affecting the thermal comfort of spaces.…”
Section: Summary Of Articles Included In the Special Issuementioning
confidence: 99%
“…Meanwhile, they summarized the recommended values of spatial characteristics and visual and smell environment indicators. Cheng et al analyzed the factors affecting the thermal comfort of green spaces [15]. They found that water and greening coverage are the primary factors affecting the thermal comfort of spaces.…”
Section: Summary Of Articles Included In the Special Issuementioning
confidence: 99%